PENGARUH MEDIA SOSIAL, PERHATIAN ORANG TUA, DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS TERPADU - Oktaviana Oktaviana; Rusno Rusno; Riril Mardiana Firdaus (Jurnal Riset Pendidikan Ekonomi, 2018)
The purpose of the study was to reveal social media, parents' attention, and interest in learning about student learning outcomes. With the existence of good social media accompanied by the attention of good parents and good learning outcomes, it will improve student learning outcomes. This study aims to determine the effect of social media, parents' attention, and interest in learning towards the learning outcomes of social studies subjects for VII grade students of Ma'arif 02 Middle School Malang. This type of research uses ex-post facto research. The population in this study were students of class VII at Ma'arif 02 Islamic Junior High School in Malang, amounting to 320 students with a research sample of 79 students. Based on the calculation results, it is known that: There is the influence of social media, parents' attention, and interest in learning towards learning outcomes. The results of multiple regression analysis revealed that the F-count value was 9.572 with a significant level of 0.000 <0.05, so it can be said that social media (X1), parents' attention (X2), and interest in learning (X3) had a simultaneous or partial influence on learning outcomes (Y).